After EMPA-REG OUTCOME and LEADER: Already a „New Era“ in Therapy of Type 2 Diabetes? - Schatz, H. (Experimental and Clinical Endocrinology & Diabetes, 2016)
Critical discussion of the cardiovascular findings with empagliflozin (EMPA-REG OUTCOME Study)and liraglutide (LEADER Study) and the consequences.
Keywords: empagliflozin; liraglutid; cardiovascular effects; new era of treatment?; add-on to metformin?